Quality of injured winter wheat seeds depending on storage conditions - Polishchuk, V.; Konovalov, D. (Scientific Progress & Innovations, 2023)
The article presents the results of studies on the influence of the term and conditions of storage of winter wheat seeds in sealed and unsealed containers in a climate chamber and storage, depending on the degree of their injury. It was found that storage of seeds for five years with varying degrees of injury led to a significant decrease in their quality. When stored in a climate chamber in a sealed container with a moisture content of 6.7 %, the seeds were stored better than in a leaky container. Thus, at a degree of injury of 79 %, the germination energy, germination and growth force of seeds in sealed containers decreased by 2, 3 and 5 %, respectively, and in leaky containers – by 7, 6 and 9 %. At the same time, the seeds fully retained their original quality indicators, even with a slight injury of 18 % under the same storage conditions. It is worth noting that with an increase in the degree of seed injury from 18 to 79 %, the quality indicators naturally decreased under all storage conditions. More injured seeds (56 and 79 %) lost their viability much faster. Also, the amount of air-dry mass of sprouts and roots decreased and the degree of leaching of extractive carbohydrates from seeds increased, especially in seed samples stored in leaky containers regardless of their degree of injur. In severely injured seeds (56 and 79 %) stored in sealed packaging both in the climate chamber and in the storage facility, viability indicators increased – the content of extractable sugars, which is associated with mechanical damage to the seed coat and removal of seeds from the post-harvest ripening state. Such seeds were less affected by pathogens. Thus, based on the experimental data obtained, it can be concluded that when laying seed stocks for long-term storage, the degree of seed injury should be taken into account, and mechanical damage to the seeds should be prevented during harvesting, post-harvest processing and storage. It is advisable to store injured seeds of valuable breeding and genetic samples at a moisture content of about 7.6 % in a sealed container.